Feasibility study of engineered geopolymer composites based high-calcium fly ash and micromechanics analysis - Zhen Yuan; Zhiming Pang; Cong Lu; Yiming Yao (Case Studies in Construction Materials, 2024)
Engineered geopolymer composites (EGC) have attracted much attention as green construction materials, characterized by strain-hardening behavior and multiple cracking capabilities. Nevertheless, the current utilization of low-calcium fly ash in EGC preparation poses a challenge in terms of long hardening time, which substantially affects the feasibility of applying EGC in engineering projects. The purpose of this study is to assess the potential for developing EGCs using high-calcium fly ash (HFA), explore the impact of sodium silicate (SS)-to-sodium hydroxide (SH) ratio on material properties, and perform a comparative analysis between EGCs fabricated with low-calcium fly ash (LFA) and HFA. SEM analysis elucidates that an increase in the SS-to-SH ratio exerts a favorable influence on matrix density, thereby augmenting overall strength. Nevertheless, this enhancement is accompanied by a notable reduction in tensile strain capacity. It was observed that EGC based on HFA (HFA-EGC) outperforms LFA-based EGC (LFA-EGC) in various aspects of mechanical properties. The effects of SS-to-SH ratio, LFA, and HFA on the mechanical properties were analyzed at the microscale using XRD and SEM, and combined with micromechanical parameters, establishing a multi-scale connection for material performance. The study offers a comprehensive analysis of how varying precursor and activator compositions affect the tensile properties.